A tecnociência no desastre : governança, expertise e poder a partir do caso Samarco - Victor José Alves Fernandes (2022)
This work aims to investigate the way in which science and technology are inscribed in decision-making processes related to the reparation resulting from the disaster engendered by the mining company Samarco, a subsidiary of the multinationals Vale S.A. and BHP Billiton, triggered by the collapse of the Fundão mining tailings dam, in the municipality of Mariana, Minas Gerais. In order to do so, I proceed as follows: using ethnography as a research strategy, I take on the examination of documents that modulate the institutional arrangement created to manage the effects of the disaster; secondly, I analyze the encounters provided by a specific modality of participation in Mariana between those victimized by the disaster and representatives of the institutions responsible for managing the disaster; lastly, I investigate the disputes around different means of identification, quantification and valuation of the losses and damages caused by the disaster. Results obtained indicate that, at first, science, technology and the notion of expertise figure as important discursive resources to obliterate conflicts and build an alleged technical inexorability of reparation policies. However, for this same reason, technoscience itself progressively becomes a field of dispute. In such scenario, judicial discretion presents itself as a fundamental decision-making instance: when conflicts resist dissolution by means of technoscientific discourse, technique is dispensed with in the name of efficiency and celerity of the legal process.